Mechanisms of Resistance to Schistosoma japonicum Infection in Microtus fortis, the Natural Non-permissive Host - Shen, Jia; Xiang, Suoyu; Peng, Mei; Zhou, Zhijun; Wu, Zhongdao (Frontiers in Microbiology, 2020)
Human schistosomiasis, which is caused by schistosomes, is a zoonosis that is difficult to control because of the many reservoir hosts. However, Microtus fortis is the only mammal that is naturally resistant to Schistosoma japonicum infection known in China, in which S. japonicum growth and development were arrested on day 12, and the worms eliminated on day 20 post-infection. In this review, we present an overview of the established and purported mechanisms of resistance to S. japonicum infection in M. fortis in comparison to Rattus norvegicus, a semi-permissive host. Clarifying the mechanism of this efficient resistance can help us to better understand host-parasite interaction and to provide better methods to control schistosomiasis.